Positive pressure matters in acoustic droplet vaporization - Samuele Fiorini; Anunay Prasanna; Gazendra Shakya; Marco Cattaneo; Outi Supponen (Physical Review Research)
Acoustically vaporizable droplets are phase-change agents that can improve the effectiveness of ultrasound-based therapies. In this study, we demonstrate that the compression phase of an acoustic wave contributes to the generation of the negative pressure that initiates vaporization. This counterintuitive process is explained by separately evaluating the contribution of the compression and rarefaction phase of the incoming acoustic wave to the acoustic pressure field inside the droplet. Our analysis unifies the existing theories for acoustic droplet vaporization under a single framework and is supported by experiments and simulations. This different interpretation can be employed to identify governing parameters that allow one to vaporize droplets using predominantly compression waves, which are safer in medical use.